2018
DOI: 10.1080/2162402x.2018.1550618
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 signaling modulates interferon-γ production by Gamma Delta (γδ) T-Cells in response to leukemia

Abstract: Gamma delta (γδ) T-cell based immunotherapy is a promising concept for the treatment of hematologic malignancies. Not only in vitro but also in early phase clinical trials, zoledronic acid (Zol) and interleukin-2 (IL-2) have been successfully used to activate human γδ T-cells and to induce clinical anti-tumor effects. Aiming to improve the effectiveness of future γδ T-cell based immunotherapies against leukemia, we analyzed the impact of programmed cell death protein 1 (PD-1) signaling, on the different phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 21 publications
0
76
2
Order By: Relevance
“… 113 , 202 , 203 PD-1 blockade with antibodies such as pembrolizumab does not significantly modulate the killing capacity 202 , 203 but enhances IFN-γ production in ZOL-activated Vδ2T cells. 203 Depending on the status of PD-1 expression on γδ T cells, combination with pembrolizumab might be envisaged for γδ T cell therapy, similar to what has recently been shown for allogeneic NK cell therapy. 204 Another example of an inhibitory receptor is NKG2A, which can be expressed together with CD94 on γδ T cells.…”
Section: Combination Matters: How To Improve γδ T Cell Therapymentioning
confidence: 98%
“… 113 , 202 , 203 PD-1 blockade with antibodies such as pembrolizumab does not significantly modulate the killing capacity 202 , 203 but enhances IFN-γ production in ZOL-activated Vδ2T cells. 203 Depending on the status of PD-1 expression on γδ T cells, combination with pembrolizumab might be envisaged for γδ T cell therapy, similar to what has recently been shown for allogeneic NK cell therapy. 204 Another example of an inhibitory receptor is NKG2A, which can be expressed together with CD94 on γδ T cells.…”
Section: Combination Matters: How To Improve γδ T Cell Therapymentioning
confidence: 98%
“…Among the reasons of these relatively modest clinical results were the skewing of γδ T cells toward a non-reactive or even a pro-tumor phenotype. For example, Hoeres et al showed that incubation of PBMCs from patients with leukemia with IL-2 and/or zoledronic acid, which are used to activate γδ T cells, induces PD-1 expression by γδ T cells and impairs their anti-tumor functions (110). Similarly, Castella et al reported PD-1 expression by γδ T cells in patients with myeloma after phosphoantigen activation (111).…”
Section: Implications For γδ T Cell-based Tumor Immunotherapymentioning
confidence: 99%
“…Aminobisphosphonate activation of γδ T cells in combination with chemotherapy or with FDA-approved antibodies is one of these axes. Hoeres et al and Castella et al showed that incubation with an anti-PD-1 antibody restores the proliferative and anti-tumor properties of Vγ9Vδ2 T cells from patients with leukemia or lymphoma (110,111). However, Castella et al then found that phosphoantigen stimulation of anergic PD-1+ Vγ9Vδ2 combined with PD-1 blockade increases the expression of PD-1 and of two other immune checkpoint molecules (TIM-3 and LAG-3), leading to a "super-anergic" state (112).…”
Section: Implications For γδ T Cell-based Tumor Immunotherapymentioning
confidence: 99%
“…The γδ T cells are susceptible to PD-1–mediated inhibition ( 186 , 187 ), and the tumor models where the vaccines were evaluated express high levels of PD-L1. The high therapeutic efficacy suggests that the vaccines partially overcome the inhibitory effects of PD-L1 upon γδ T cells.…”
Section: The Potential Of γδ T Cells In Targeting the “Glycocode”mentioning
confidence: 99%